Perancangan Antena Mikrostrip Dual-Band Patch Persegi Panjang Plannar Array 6 Elemen Dengan Defected Ground Structure Berbentuk Segitiga Untuk Jaringan Komunikasi Nirkabel 5G - Muhammad Ibnu Hidayat; Yusnita Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
In this paper, a six-element dual-band antenna array for 5G wireless communication network is presented. The proposed antenna’s size is 25 x 35